Low cholesterol levels are good markers for central hypothyroidism in case with dialysis using roxadustat - Serina Kita; Hiroshi Okuyama; Takaya Kondo; Mizuki Hayashi; Shinichiro Nakao; Toshitaka Sawamura; Keiji Fujimoto; Atsushi Nakagawa; Hitoshi Yokoyama; Kengo Furuichi (Clinical Case Reports)
Key Clinical Message Recently, hypoxia‐inducible factor prolyl hydroxylase (HIF‐PH) inhibitors have been used for renal anemia, but side effects have also been reported. We report on the association of central hypothyroidism and cholesterol with roxadustat. Based on this case and previous reports, we believe that patients receiving roxadustat should have their thyroid function and cholesterol levels checked regularly.